Otrā un trešā konjugācija agrākajās latviešu gramatikās - Fennell, Trevor G. (Baltistica, 1989)
THE SECOND AND THIRD CONJUGATIONS IN THE EARLIEST LATVIAN GRAMMARSThe earliest writers on Latvian inherited much of their framework from Latin, but many questions required independent empirical analysis, especially in verb morphology. The present tense contrast between dzied-u and strād-āju proved particularly troublesome.Rehehusen (1644) seems to have been hardly aware of the problem. Büchner (c. 1670) did little more than note the two types. Langius (1685) did not refer to the problem at all. Dreszell (1685) recognized the distinction between monosyllabic and polysyllabic infinitives, but his treatment of polysyllables was highly confused. Adolphi (1685) provided the first extensive treatment, but yet left many details unresolved. The „Dispositio imperfecti…“ (1732) offered a new theoretical approach in which the present (not the infinitive) serves as the starting-point, but this innovation, both in practice and in theory, proved to be unworkable. The next grammar, "Lotavica Gram-matica” (1737), reverted to a re-statement of Adolphi’s views.It is only with Stender (1761), who, ironically, expressed grave doubts about the organization of polysyllables, that further real progress is made. His description is inferior to the modern theory in minor respects only. His work stands as the culmination of the first phase of research on the Latvian verb.